Calculation of beta radiation absorbed dose from three beta emitters in nuclear physics lab - Hussien Abid Ali Baker; Ibtisam Jaafar Abd Ali (Al-Qadisiyah Journal of Pure Science, 2018)
The aim of this project is to determine the amount of absorbed dose received by radiation worker from beta emitters. Three beta emitters where enrolled in this project ,Co60 ,Cs137  and Sr90,the parameters that which involved in this project are, activity of radioactive source and distance from the source(cm).Calculation were done to calculate the dose rate using computer based program that can accomplished large processes at very high speed .The result show significant high dose when compared with these results obtained from projects that dealing with the dose from naturally occurring radioactive source in environment.